Sociologies of terrorism: Holographic metaphors for qualitative research. (June 2016) - Howie, Luke; Kelly, Peter
In the years following 9/11, we spoke to residents of an Australian city who had witnessed the attacks on television in a research process that we came to describe as holographic. This metaphor emerged as we struggled to represent data generated in these interviews. This struggle over meaning provoked us to ask fundamental questions about the collection of knowledge in sociologies of terrorism – about the encounter of Self–Other in interviews; the embodied, situated location of researcher and researched in such encounters; how this location exists in particular configurations of time and space but is continually re-animated in other configurations of time and space as processes of meaning-making unfold in the production of a variety of texts (recordings, transcripts, papers, articles). To study terrorism, researchers grapple, knowingly or not, with an unstable and volatile concept. It is a volatility that should be embraced, not marginalised, in sociological research into terrorism.